INTERNATIONAL EXPERIENCES IN IMPROVING THE FINANCING OF INVESTMENT PROJECTS IN SPECIAL ECONOMIC ZONES - Xonimqulov Islom Ergash og‘li; Egamov Otabek; Scientific Supervisor: Phd, Umirzokov Jasur (Web of Journals Publishing, 2024)
This article examines international experiences aimed at improving the financing mechanisms of investment projects within the framework of Special Economic Zones (SEZ). Special economic zones play a decisive role in stimulating economic growth and attracting foreign investments. However, financing these projects often presents challenges due to their unique characteristics and requirements. By examining various international approaches and strategies, this paper aims to provide insight into effective financing models and mechanisms that can be adapted and implemented to support investment projects within SEZs. Through case studies and comparative analysis, it highlights successful practices, identifies key factors influencing financing outcomes, and provides recommendations for policymakers, investors, and stakeholders involved in SEZ development initiatives.
Keywords: Special Economic Zones (SEZ); Investment projects; Financing mechanisms; International experiences; Economic development.